Exorcizing Wechsler's Ghost: The Influence of the Model Penal Code on Death Penalty Sentencing Jurisprudence - Covey, Russell Dean (2004)
The constitutional law of capital sentencing currently is torn between its past and its future, its inheritance of a utilitarian, offender-based, sentencing theory and the powerful contemporary resurgence of retributivism as the dominant justification for criminal punishment. The basic procedural and jurisprudential structures all originated as the offspring of an explicitly nonretributive penal theory crafted in large part by Herbert Wechsler and codified in the Model Penal Code. To bring death penalty procedure more in line with contemporary understandings of the death penalty's theoretical and moral justification, the ghost of Herbert Wechsler must be exorcized from the constitutional law of capital sentencing. Abolition of the death penalty is likely the only sure way to root out the myriad sources of discrimination and arbitrariness that currently plague administration of the death penalty. Short of that, rationalization of sentencing procedures so as to make them more consistent with the most commonly recognized justification for keeping the system in place - retributivism - might help ensure that only those fully culpable for the worst crimes are subject to its reach